1984
DOI: 10.1007/bf01398350
|View full text |Cite
|
Sign up to set email alerts
|

Sorption removal of oxygen by refractory materials from iron-nickel melts

Abstract: The refractory lining in which a metal is smelted has a significant effect on the properties of the metal.An equilibrium concentration of oxygen, which depends on the chemical nature of the crucible material, is established in the molten metal when subjected to a long dwell in the crucible [i]. Under actualconditions, the induction crucible furnace with intense electromagnetic perturbation and a relatively large specific interface surface between the metal and lining, which helps to bring the system (metal-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, Turdzhuman et al [12] showed that oxygen migration from the steel into the MgO and AI20s based refractories amounts to 2.10-3-10 -2 %/mln. This value coincides with the diffusional flux (rate) calculated here.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Turdzhuman et al [12] showed that oxygen migration from the steel into the MgO and AI20s based refractories amounts to 2.10-3-10 -2 %/mln. This value coincides with the diffusional flux (rate) calculated here.…”
mentioning
confidence: 98%
“…Based on the residual oxygen content in the steel and the FeO content obtained from the liquidus lines at 1873~ in the FeO-oxide systems, we calculated the actual distribution coefficient of oxygen, and evaluated the sorption ability of the refractory [12] from the ratio The results are shown in Table i.…”
mentioning
confidence: 99%